PENGEMBANGAN PROGRAM CAI DENGAN STRATEGI REMIDIASI KESALAHAN - Herman Dwi Surjono (Jurnal Kependidikan, 1999)
Abstract The purpose of this research was to develop, to evaluate, and to investigate the effectiveness of error remediation CAI lesson. The CAI lesson was developed using error remediation strategies. An experimental study involving 30 students of electrical department at vocational college of FPTK IKIP Yogyakarta was conducted. Questionnaires, evaluation sheets, and achievement tests were used to gather data. The validity and reliability of the research instrument were establish. There were 75% to 94% of the students expressed that the CAI lesson concerning four aspects: subject matter, presentation, student interaction and program interaction were good. The achievement of the students using the error remediation CAI lesson was higher significantly (α=0.05) than those of the students using the regular SPR lesson. Keywords: computer-assisted instruction (CAI), error remediation, tutorial